PENGARUH TRADISI AYUN BAPUKUNG SUKU BANJAR TERHADAP KUALITAS TIDUR BAYI DI PUSKESMAS ENOK PROVINSI RIAU - Nursifa; Evi Hasnita; Siswanto Pabidang (JOMIS (Journal of Midwifery Science), 2026)
ABSTRACT  The quality of a baby's sleep plays an important role in growth and development. Ayun bapaukung is a unique tradition of the Banjar Tribe in putting babies to sleep which is considered to make babies sleep better. The study aims to determine the influence of the banjar tribe bapukung swing tradition on the quality of infant sleep. The research design used mixed methods with an embedded experimental design model. Quantitative research design quasy experimental with control group with a sample of 36 infants aged 3-12 months with purposive sampling. The qualitative sample was 5 baby mothers, 4 health workers and 3 traditional leaders/community leaders. The intervention of bapukung swing for 7 days and sleep habits were measured with the BISQ questionnaire. The analysis uses Paired samples t-test and Independent samples T-test. The results of the study obtained an average value of the baby's sleep quality before the bapukung swing was 7.88, after the bapukung swing increased to 10.11 and there was an influence of the banjar tribe bapukung swing tradition on the quality of the baby's sleep at the Enok Health Center with a p-value of 0.002. Ayun bapukung can be recommended as an effective non-pharmacological intervention to improve the quality of infant sleep, with education from health workers to infant mothers so that the practice is carried out safely and maintains the safety and comfort of the baby.